Annotated catalogue and checklist of Gerromorpha, Nepomorpha, and Leptopodomorpha (Hemiptera: Heteroptera) of Lebanon, with new records - Cianferoni, Fabio; Dia, Aref (Zootaxa, 2025)
An annotated catalogue and a checklist for three infraorders of aquatic, semi-acquatic and water-dependent true bugs (Hemiptera: Heteroptera: Gerromorpha, Nepomorpha, and Leptopodomorpha) of Lebanon are provided. Data originate from an extensive ecological survey of the Lebanese river systems, the revision of the historical collection by Enrico Festa of 1893 (records published by E. Giglio-Tos but overlooked by most subsequent authors), and the examination of additional material from further entomological collections. This study led to 12 country records: Rhagovelia infernalis africana Lundblad, 1936; Gerris maculatus Tamanini, 1946; Micronecta pusilla (Horváth, 1895); M. scutellaris (Stål, 1858); M. wui alkani Hoberlandt, 1952; Corixa punctata (Illiger, 1807); Sigara mayri (Fieber, 1860); Anisops debilis perplexus Poisson, 1929; Anisops varius Fieber, 1851; Notonecta meridionalis Poisson, 1926; Plea cryptica Raupach, Charzinksi & Hendrich, 2024; and Saldula pallipes (Fabricius, 1794). A second species of Hebrus is reported for the country, but without specific attribution, being a female. Futhermore, four species, based on doubtful or single records for Lebanon, were confirmed: Mesovelia vittigera Horváth, 1895; Aquarius p. paludum (Fabricius, 1794); Sigara n. nigrolineata (Fieber, 1848); Anisops s. sardeus Herrich-Schäffer, 1849. A further record of an undescribed species of Saldula, already reported for Lebanon, Israel, and Turkey, is also provided, however, it was not possible to proceed with the description becauses it is a single female. The analytical review of the literature and historical material enabled us to pre-emptively or definitively exclude nine taxa from the Lebanese fauna: Mesovelia furcata Mulsant & Rey, 1852 (also excluded for Syria and Israel); Hebrus pusillus (Fallén, 1807); Rhagovelia nigricans (Burmeister, 1835); Velia rivulorum (Fabricius, 1775); Gerris gibbifer (Schummel, 1832); Micronecta minutissima (Linnaeus, 1758); Arctocorisa carinata (C.R. Sahlberg, 1819); Notonecta glauca Linnaeus, 1758; and Saldula saltatoria (Linnaeus, 1758). The first country records for Plea cryptica are provided also for Armenia and Italy. Moreover, a new synonymy, i.e. Micronecta (Basileonecta) scutellaris pubescens Hutchinson, 1940 syn. nov. of Sigara scutellaris Stål, 1858, is proposed.